Can Lean Six Sigma make UK public sector organisations more efficient and effective?. Issue 7 (12th September 2016) - Antony, Jiju; Rodgers, Bryan; Gijo, E.V.
Abstract : Purpose: The purpose of this paper is to demonstrate the widespread but fragmented application of Lean Six Sigma within the UK public sector, providing the context of some of the challenges faced within the sector as well as some of the successful applications of Lean Six Sigma. The paper fundamentally seeks to challenge the concept that Lean Six Sigma is not suitable for use in the public sector. Design/methodology/approach: A summary of the challenges facing the public sector is shown from current literature and this is presented as drivers for change. A number of successful applications of Lean Six Sigma are then evidenced demonstrating examples across areas of the public sector. Findings: This paper concludes that while Lean Six Sigma is applicable to the UK public sector additional work is required to better evidence the benefits and return on investment that can be delivered as well as considering more holistic approaches on an agency wide basis. Research limitations/implications: This paper seeks to contribute to and broaden the limited body of evidence of the applicability of Lean Six Sigma to the UK public sector and identifies areas for further research and review. Practical implications: Understanding the applicability of Lean Six Sigma affords opportunities to public sector agencies in the current budget climate but additionally affords ways in which quality of service can be enhanced. In some cases, it provides opportunities to meet new statutory requirements around community empowerment. Originality/value: The paper contributes to the body of evidence that demonstrates the effectiveness of Lean Six Sigma within the public sector and suggests opportunity for those agencies to meet funding challenges faced across the UK.